Pengaruh Media Pembelajaran Visual Basic Application (VBA) Microsoft Excel Terhadap Motivasi Belajar Siswa SMP Kelas VII Pada Materi FPB dan KPK - Siti Sarah Khodijah; Dara Kartika Dewi; Siti Chotimah (Departement of Mathematics Education, 2020)
This research aim to analyzing student’s motivation in learning mathematics in FPB and KPK material assisted by Microsoft Excel Visual Basic Application (VBA) learning media. In this study, the method used was a quasi experiment with percentage quantitative descriptive techniques. The population in this study were all junior high school students in West Bandung Regency with the sample used were 38 students of class VII-5 of SMPN 1 Sindangkerta. Research data collection uses a questionnaire on student motivation scale in mathematics learning aided by Microsoft Excel Visual Basic Application (VBA) which contains 20 statements each of 10 positive and negative statements. The results of the analysis in this study can be concluded that there is a positive impact on students' motivation to learn mathematics with the help of Microsoft Excel Visual Basic Application (VBA). This can be seen from the average percentage of answers of students who think strongly agree on a positive statement as much as 26.16%, then the response of agree produces an average of 63%, for the response of 7% disagree, while for a strongly disagree response of 3.83%.